Influence of Gestational Hypertension on Cardiovascular Health Behaviors and Factors. (29th March 2022) - Zhao, Haiyan; Wu, Yuntao; Sun, Junyan; Zu, Changhao; Ruan, Chunyu; Cui, Kai; He, Honghong; Wu, Shouling; Peng, Xiaojing
Abstract : Objective . A survey was conducted to analyze the epidemiological differences in ideal cardiovascular health (CVH) behaviors and factors after delivery in females with and without gestational hypertension (GH) and evaluate the influence of GH on cardiovascular health behaviors and factors. Methods . The present study adopted a cross-sectional design. A total of 4620 female workers who gave birth between 1976 and 2012 and received the annual health examination (2012 to 2013) at hospitals belonging to the Kailuan Medical Group were recruited. These subjects were divided into the GH group and non-GH (NGH) group, depending on whether they were combined with GH or not at delivery. The epidemiological differences in CVH behaviors and factors were compared between the two groups. Result . In both groups, the percentage of subjects achieving ideal smoking status was the highest, while the percentage of subjects achieving an ideal level of physical activity was the lowest among all behaviors and factors. Compared with the NGH group, the percentages of subjects achieving each of the seven ideal CVH metrics decreased in the GH group. The percentages of subjects achieving ideal body mass index (BMI), blood pressure, blood glucose level, and cholesterol level were significantly lower in the GH group than in the NGH group (P < 0.05 ). The percentage of subjects with an ideal level of physical activity was higher in the NGH group than in the GH group. After stratification by age, the percentages of patients achieving ideal BMI, blood pressure, and blood glucose decreased with age regardless of the history of GH (P < 0.05 ). In the younger age group, the percentage of subjects with GH achieving ideal body mass index was significantly lower than that of those without GH. Conclusion . Compared with females without GH, those with GH had higher BMI, blood pressure, blood glucose level, and cholesterol level among the seven CVH metrics surveyed.